Isolation and identification of non‐Saccharomyces yeasts and their flavour characteristics while brewing Yinhong plum wine - Lei, Yu; Li, Tian; Chen, Li; Deng, Meng‐Sheng; Jin, Lei; Li, Yu‐Hao; Li, Dong (Flavour and fragrance journal, 2024)
The objective of this study was to screen non‐Saccharomyces yeast suitable for enhancing the aroma of Yinhong plum wine. Five non‐Saccharomyces yeasts with strong ester‐producing ability, namely, Wa3 (Wickerhamomyces anomalus), Hu12 (Hanseniaspora uvarum), Pk2A2, PkW2 and PkY2 (Pichia kluyveri), were selected from various naturally fermented fruit juices for molecular biological identification, analyses of physiological characteristics and tolerance and determination of their effects on the flavour of Yinhong plum wine. Analysis of brewing characteristics showed that they differed in their abilities of producing acetic acid, hydrogen sulfide, killer activity and tolerance. Among them, Wa3 showed the best tolerance to high concentrations of alcohol, sugar and SO2. Compared to the control Saccharomyces cerevisiae FX10, Yinhong plum wine fermented with non‐Saccharomyces yeast exhibited a decrease in alcohol content, while residual sugar, glycerol content and the types and quantities of volatile compounds all showed an increase. Among the fermented wines, PkY2 generated the highest content of ester compounds in the fermented wine, which was 5.66 times higher than that generated by the control. The compounds produced by PkY2 were closely related to various ethyl and acetate odour‐active compounds (odour‐active value >1), which could impart a rich floral and fruity aroma to Yinhong plum wine. Sensory analysis revealed that both floral and fruity aromas were significantly increased in Yinhong plum wine fermented by non‐Saccharomyces yeasts, with the highest scores of floral and fruity aromas for PkY2. In conclusion, a Pichia kluyveri strain, PkY2, with excellent brewing characteristics and potential for enhancing the aroma of Yinhong plum wine was identified. Pichia kluyveri PkY2 enhances Yinhong plum wine with superior ester production, elevating floral and fruity aromas, offering a unique and appealing sensory experience.